PERKEMBANGAN PENDIDIKAN DI NEGARA JEPANG PASCA PERANG DUNIA II DAN RELEVANSINYA TERHADAP PEMBELAJARAN SEJARAH DI SEKOLAH MENENGAH ATAS PROGRAM STUDI PENDIDIKAN SEJARAH FKIP UNS - Wahyuni, Sri; Agung S, Leo; Wahyuni, Sri (Candi, 2018)
The objective of research was to find out: (1) the condition of education in Japan before Second World War, (2) the condition of education in Japan post-Second World War, and (3) the Relevance of education development in Japan post-Second World War to Historical learning in Senior High School based on the curriculum of 2013. The method employed in this research was historical one. Historical method was the process of examining and analyzing critically the recording and relics of the past. The preliminary stage conducted in historical research process was data collection or heuristic one. The data of research collected included primary and secondary data relevant to Education in Japan Post-Second World War. The data obtained was then analyzed. Data analysis started with verification or critique, interpretation and then historiography explanation.  Considering the result of research, the following conclusions could be drawn. (1) Japan Meiji Restoration brought about considerable change in Japan people? life particularly in education. Public elementary education started to be given priority, a number of universities and middle education institution and college was established. (2) Education System in Japan before Second World War included Elementary School in 6-year age constituting compulsory education, junior high education for 5 years, senior high education for 3 years, and university education for 3 years. (3) Japan Education system post-Second World War basically involved elementary school (six years), junior high school (three years), senior high school (three years), and university (four years). Education was compulsory in nature only for nine years, six in elementary and three in junior high schools. (4) Education policy and development in Japan was related to the material of Indonesian heroism revival and nationality during Japan occupation and colonialism age particularly the effect of education field on Indonesia.